Implementasi akad Rahm pada Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BMT NU Jawa Timur Cabang Genteng Banyuwangi - Syafly, Iqbalul Luayyi; Khoiruddin, Muh.; Rachmawati, Afria (CV. Lentera Literasi Indonesia, 2025)
This study aims to describe the partners' understanding of the rahn contract and the concept of daily ujrah, as well as to analyze the role of KSPPS BMT NU Genteng Branch, Banyuwangi, in empowering the ummah's economy through the implementation of the rahn contract. The method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results show that some partners do not fully understand the mechanism of daily ujrah in the rahn contract, which leads to complaints at the time of repayment. This lack of understanding is caused by low Islamic financial literacy and the suboptimal dissemination of information by the institution. On the other hand, BMT NU Genteng Branch plays a strategic role in providing fair and quick access to Sharia-based financing, especially for lower-middle-class communities who do not have conventional collateral. The rahn contract not only serves as an emergency financial solution but also functions as a tool for empowering the ummah’s economy in accordance with the principles of justice, mutual help (ta’awun), and balance in Islamic economics.